The criminal offense in Colombian criminal law : Analysis of Article 9 of the Penal Code (2013)
Article 9 of the Criminal Code defines, as system governing principle, the punishable behavior concept. The following text, questioning the uncritical reception of foreign theories to the legal system, (also Codes, rules, entre otros.) presents some of th